ANALISIS PENERAPAN ETIKA BISNIS DALAM TRANSAKSI PERDAGANGAN DI RUMAH MAKAN : (Studi Kasus Rumah Makan Nasi Goreng Pakdhe Desa Sumengko Kecamatan Wringinanom Kabupaten Gresik) - Muthi Dwika Ningrum; Fitri Komariyah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Currently, there is a prevalence of unethical behavior, particularly in the restaurant business. The proper application of business ethics ensures that business activities remain in line with norms and regulations. This research is motivated by the presence of businesses that bring buyers and sellers together. The objectives of this study are to determine (1) how to apply business ethics in trade transactions at Nasi Goreng Pakdhe Restaurant and (2) the nature of trade transactions at Nasi Goreng Pakdhe Restaurant. This research employs a qualitative approach, gathering information through interviews, observations, and documentation before subjecting it to descriptive analysis. Both primary and secondary data sources are used in this research. The research findings indicate that the business transactions at Nasi Goreng Pakdhe Restaurant align with its vision and mission, which include a commitment to honesty in business affairs, providing the best service to customers, engaging in fair competition, and avoiding excessive profit generation. Nasi Goreng Pakdhe Restaurant also practices ethical business principles, such as upholding product quality, demonstrating strong leadership, and giving employees, staff, and customers the opportunity to provide feedback and suggestions.